Impact of Cation Concentration on Graphene Oxide Properties Fabricated from Disposed Batteries - Dong-Nghi Le; Tien-Luat Nguyen; Phuong V Pham; Tuan-Huu Nguyen; Thuy-Hong-Lam Ngo; Thien-Trang Nguyen; Van-Cuong Pham; Anh-Vu Phan-Gia; Huy-Binh Do (Journal of Technical Education Science, 2024)
Disposed batteries contain the hazardous sources that directly impact on the environment. Proper disposal of used batteries is a vital matter because of toxit component found in types of batteries. This study focuses on the reutilization of the disposed Zn-battery graphite to produce graphene oxide (GO) via electrochemical exfoliation. The influence of various electrolytes on the exfoliation process was investigated, and the optimal ID/IG values in Raman spectra were determined as 2.5% for KOH. Scanning electron microscopy (SEM) images confirmed the presence of multi-wall graphene oxide in the exfoliated samples. X-ray diffraction (XRD) spectra displayed a broadening of the peak at 2θ = 26.5°, further supporting the successful formation of graphene oxide. The exfoliated graphene oxide was found not to contain any toxic elements. This highlights the potential of using disposed batteries in producing low cost graphene oxide. The study contributes to environmental protection by repurposing graphite rods and reducing industrial waste.